On Ɱicro α- generalized closed and Ɱicro semi- generalized closed in Ɱicro -topological spaces - Saja S. Mohsen; Taha H. Jasim (Tikrit Journal of Pure Science)
We're going to study a new definitions in this paper that’s are  generalized  ,  generalized ,  generalized  and  generalized . Also, we show the relationships between them in illustration diagram and gives some results and examples.